Distinct forms of cholinergic modulation in parallel thalamic sensory pathways - Mooney, D. M. (National Academy of Sciences, 2004)
Mammalian thalamus is a critical site where early perception of sensorimotor signals is dynamically regulated by acetylcholine in a behavioral state-dependent manner. In this study, we examined how synaptic transmission is modulated by acetylcholine in auditory thalamus where sensory relay neurons form parallel lemniscal and nonlemniscal pathways. The former mediates tonotopic relay of acoustic signals, whereas the latter is involved in detecting and transmitting auditory cues of behavioral relevance. We report here that activation of cholinergic muscarinic receptors had opposite membrane effects on these parallel synaptic pathways. In lemniscal neurons, muscarine induced a sustained membrane depolarization and tonic firing by closing a linear K(+) conductance. In contrast, in nonlemniscal neurons, muscarine evoked a membrane hyperpolarization by opening a voltage-independent K(+) conductance. Depending on the level of membrane hyperpolarization and the strength of local synaptic input, nonlemniscal neurons were either suppressed or selectively engaged in detecting and transmitting synchronized synaptic input by firing a high-frequency spike burst. Immunohistochemical and Western blotting experiments showed that nonlemniscal neurons predominantly expressed M2 muscarinic receptors, whereas lemniscal cells had a significantly higher level of M1 receptors. Our data indicate that cholinergic modulation in the thalamus is pathway-specific. Enhanced cholinergic tone during behavioral arousal or attention may render synaptic transmission in nonlemniscal thalamus highly sensitive to the context of local synaptic activities.